The MELD-XI score predicts 3-year mortality in patients with chronic heart failure - Lin, Zebin; Liu, Xia; Xiao, Li; Li, Yin; Qi, Chenlu; Song, Siqi; Zhao, Yiping; Zou, Lili (Frontiers in Cardiovascular Medicine, 2022)
Objectives The relationship between the MELD-XI score, a modified version of the MELD score, and the long-term prognosis of hospitalized patients with chronic heart failure is unclear. The aim of this study was to determine the long-term prognostic relationship of MELD-XI score in patients with chronic heart failure. Methods This is a retrospective cohort study of patients with chronic heart failure who were initially hospitalized in the Second Affiliated Hospital of Chongqing Medical University from February 2017 to December 2017. The primary clinical outcome was all-cause mortality within 3 years. Cox regression and lasso regression were used to screen variables and build a prognostic model. Combined with the MELD-XI score, the final model was adjusted, and the predictive ability of the model was evaluated. Survival curves were estimated using the Kaplan–Meier method and compared by the log rank test. Results A total of 400 patients with chronic heart failure were included (median age 76 years, 51.5% female). During the 3-year follow-up period, there were 97 all-cause deaths, including 63 cardiac deaths. Six characteristic variables (NT-proBNP, BUN, RDW CV, Na+ and prealbumin) were selected by univariate Cox regression and lasso regression. Survival analysis results showed that elevated MELD-XI score at baseline predicted the risk of all-cause mortality at 3 years in patients (HR 3.19, 95% CI 2.11–4.82, P < 0.001; HRadjusted 1.79, 95% CI 1.09–2.92, P = 0.020). Subgroup analysis showed that MELD-XI score still had prognostic value in the subgroup without chronic kidney disease (HR 3.30 95%CI 2.01–5.42 P < 0.001; HRadjusted 1.88 95%CI 1.06–3.35 P = 0.032, P for interaction = 0.038). Conclusions This study proved that the MELD-XI score at admission was related to the poor prognosis of hospitalized patients with chronic heart failure within 3 years.